Intelligent Transport Systems - possibilities and effects of their application in cities - example of Lodz - Szymczyk, Maria (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
The main objective of the study is to present the benefits and opportunities arising from the presence of Intelligent Transport Systems in Łódź. The first part of this chapter explains the concept of Smart City and its essence in the modern world. Then the question of Intelligent Transport Systems and their development path was raised. The empirical part presents modern transport systems introduced in Łódź and the effects of their application. The results of a survey conducted on drivers moving around Łódź and people using local public transport were also taken into account.